Determinación del grado de regeneración hepática ante tres diferentes técnicas de hepatectomía Parcial (Veterinary Science, 2017)
After the left hepatic lobectomy the authors compared the liver regeneration by practicing three different techniques: non vascular exclusion, partial vascular éxclusion and total vascular exclusion. Nine pigs separated in three gloups are used as expenmental animals. The results are analysed based on the histopathology (mitotic index) and the hepatic enzyms. The conclusion is that there doesn't exist any difference in the liveer regeneration degfee between the compared techniques
Keywords: Surgery; Hepatectomy; Pigs